Prophetic Medicine (Al-Tibb Al-Nabaw?): is Historicity or Fiction? - Ozturk, Levent (European Journal of Multidisciplinary Studies, 2016)
At the present time, it is obvious that the attention to alternative, protective and complementary applications of medicine has increased and in this sense there is a special curiosity to the case, Prophetic Medicine “al-Tibb al-Nabaw?”. The content of this literature known under the headline of Prophetic Medicine “al-Tibb al-Nabaw?” that we come across from the 13th century, have not examined scientifically yet and it gains popularity as a reflection of love to Prophet Muhammad and Sunnah perception. Additionally, nowadays we increasingly witness to some treatment modalities and some herbal drugs associated to the Prophetic Medicine “al-Tibb al-Nabaw?” and all these practices are given a different meaning (sacred). This situation did not only create information convergence which obstacle retaining historical facts in the correct way but also, more importantly gained a new dimension that threat human health through misinformation and false application. Multidimensional researches such as history of science, history of civilization researches, laboratory studies, and collaborative work and effort of committees that contains different approaches from different countries, are needed to evaluate the information that we come across under the name of Prophetic Medicine “al-Tibb al-Nabaw?”. In this paper, we are going to try to argue what the concept of Prophetic Medicine “al-Tibb al-Nabaw?” states, how the literature related to this area in the historical time streaming, and the content of it.
Keywords: Al-Tibb al-Nabawī, Prophetic Medicine, Islamic Medicine, Alternative Medicine, Complementary Medicine.